PERAN HEXAGON FRAUD DALAM MENDETEKSI FRAUD PENGELOLAAN DANA DESA DENGAN MATERIALISME SEBAGAI PEMODERASI - Shella Gilby Sapulette (JURNAL LENTERA AKUNTANSI, 2022)
This study aims to examine the influence of pressure, opportunity, rationalization, ability, arrogance, and collusion in detecting village fund management fraud with materialism as the moderator. The population in this study are all village/traditional state apparatus in Ambon City, totaling 15 states, namely: 3 customary lands in each sub-district. The sample consisted of 66 respondents consisting including the Village head, Secretary of the village, Head of Administration and General Affairs, Head of Finance, Head of Planning and Development, Head of Government, Head of Services and Head of Empowerment. The method of analysis in this study is path analysis using PLS. The results of the study prove that the variables pressure, rationalization, ability, arrogance, and collusion do not affect village fund management fraud, opportunity affects village fund management fraud, materialism strengthens the effect of pressure, opportunity, and arrogance on village fund management fraud, but does not strengthen the effect of rationalization and collusion against village fund management fraud.Keywords: pentagon fraud, materialism, management village fund, fraud